Factors contributing to accuracy in the estimation of the woody canopy leaf area density profile using 3D portable lidar imaging - Hosoi, Fumiki (Journal of experimental botany, 2007)
Factors that contribute to the accuracy of estimating woody canopy's leaf area density (LAD) using 3D portable lidar imaging were investigated. The 3D point cloud data for a Japanese zelkova canopy [Zelkova serrata (Thunberg) Makino] were collected using a portable scanning lidar from several points established on the ground and at 10 m above the ground. The LAD profiles were computed using voxel-based canopy profiling (VCP). The best LAD results [a root-mean-square error (RMSE) of 0.21 m(2) m(-3)] for the measurement plot (corresponding to an absolute LAI error of 9.5%) were obtained by compositing the ground-level and 10 m measurements. The factors that most strongly affected estimation accuracy included the presence of non-photosynthetic tissues, distribution of leaf inclination angles, number (N) of incident laser beams in each region within the canopy, and G(theta(m)) (the mean projection of a unit leaf area on a plane perpendicular to the direction of the laser beam at the measurement zenith angle of theta(m)). The influences of non-photosynthetic tissues and leaf inclination angle on the estimates amounted to 4.2-32.7% and 7.2-94.2%, respectively. The RMSE of the LAD estimations was expressed using a function of N and G(theta(m))